A novel approach for ultrafast and highly sensitive carbon monoxide gas sensor based on PEDOT/GO nanocomposite. (1st March 2023) - Farea, Maamon A.; Mohammed, Hamed Y.; Shirsat, Sumedh M.; Tsai, Meng-Lin; Murshed, Mohammad N.; El Sayed, Mohamed E.; Naji, Sufyan; Samir, Ahmed; Alsharabi, Rim M.; Shirsat, Mahendra D.
Abstract: An ultrafast and highly sensitive carbon monoxide gas sensor based on PEDOT/GO nanocomposites has been addressed in this work. A new approach was utilized to materialize PEDOT/GO via a straightforward and inexpensive polymerization in the presence of GO. Many characterization techniques, including FE-SEM, AFM, TGA, XRD, FTIR, Raman spectroscopy, and UV–Vis spectroscopy, have been utilized to confirm the successful formation of the PEDOT/GO nanocomposite. Moreover, the chemosensitivity modality has been used to measure the materials' resistivity and sensing performance. The PEDOT/GO-based sensor exhibits excellent sensitivity when exposed to a wide range of CO concentrations, from 20 ppm to 270 ppm. Our experimental outcomes demonstrated that incorporating PEDOT into GO enhanced the sensor sensitivity (from 16% for pure PEDOT to 44% for composite), which resulted in quick response/recovery times (43 s/42 s) and exceptional long-term stability at room temperature. Based on the results of this work, it seems likely that the proposed sensor, with its low cost, simple development process, and excellent sensing performance, could be a good candidate for real-time CO detection. Graphical abstract: Image 1 Highlights: The PEDOT/GO nanocomposite-based CO gas sensor is proposed for the first time. Incorporation of GO to PEDOT significantly improves CO sensing performance. The PEDOT/GO nanocomposite-based CO gas sensor exhibited excellent performance at room temperature.